P02 Development and validation of a Novel ICP-MS method to quantify different copper species in human plasma from patients with wilson disease. (20th September 2022) - Ala, Aftab; Liang, Tao; Zhang, Haiting; Zhang, Linwen; Moseley, Scott; Guo, Ping; Chen, Meng; Hall, Tracey; Li, Ming; Swenson, Eugene; Pan, Wei-Jian; Meltzer, Brian; et al.
Abstract : Background and Aims: Wilson disease (WD) is a rare autosomal recessive genetic disorder. Functional mutation of ATP7B causes inadequate loading of copper (Cu) into ceruloplasmin (CP) and defective Cu excretion into bile, resulting in Cu accumulation in liver and other organs. Currently, WD treatment monitoring lacks reliable and fully validated bioanalytical methods. The calculated non-CP Cu (NCC) method assumes a CP-Cu:Cp ratio of 6:1 and can yield negative NCC values, which are biologically implausible. A direct assay is needed to monitor NCC, especially for patients treated with an investigational Cu-binding agent, ALXN1840 (bis-choline tetrathiomolybdate), which mobilizes tissue Cu, contributing to a non-bioavailable pool of circulating Cu. Method: A novel method utilizing immunocapture of CP, followed by chelation and filtration to isolate different Cu fractions subject to ICP-MS analysis ( figure 1 ) was developed to fractionate and directly quantify multiple Cu species from human plasma. It permits measurement of CP-protein via LC-MS method and Cu species including CP bound Cu (CP-Cu), direct NCC, and labile bound Cu (LBC) via one workflow. Methods were validated for precision, accuracy, selectivity and stability following the FDA guidance for Bioanalytical Method Validation. A monoclonal anti-CP antibody was screened and selected for long-term assay use. Samples from healthy volunteers and from patients with WD were assessed for the Cu concentration in the CP fraction and the CP-Cu:Cp ratio. Results: Full validations were successfully performed for each Cu fraction as well as CP-protein and showed a linear range from 5–1000 ng/mL (0.08 – 15.75 µM) for CP-Cu, direct NCC, LBC, and 5.00 – 800 µg/mL (0.03 – 5.97 µM) for CP-protein. The mean [95% confidence interval] for the CP-Cu:CP ratio was 4.68 [4.35, 5.00] in healthy volunteers and 4.09 [3.36, 4.82] in patients with WD, both being below the assumed ratio of 6. Conclusion: Conventional calculated NCC is inaccurate and cannot be used for therapeutic guidance for WD. A novel method was developed that utilizes an immunocapture step and subsequent quantification of various fractions, including CP-Cu, direct NCC, LBC, and CP-protein. Validation data met defined acceptance criteria in terms of precision, accuracy, selectivity and stability. The assay is precise and reproducible and is valuable for accurate quantification of CP-Cu:CP-protein ratio, direct NCC and LBC, which may benefit WD therapy development.